2007
DOI: 10.1111/j.1365-3083.2007.02000.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and In vitro Control of Leishmania mexicana due to Garlic‐induced NO Production

Abstract: Leishmania mexicana is the main causal agent of cutaneous leishmaniasis in the Yucatán peninsula in Mexico. Control of this disease is associated with a Th1‐type immune response and garlic extract has been reported as a Th1 immunomodulator in BALB/c mice infected with Leishmania major. In this study, we investigated the effect of garlic extracts on L. mexicana infection in vivo and in vitro. Garlic extract reduced footpad lesions in L. mexicana‐infected BALB/c mice by inducing IFN‐γ production from T cells. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
2
27
0
2
Order By: Relevance
“…An immunomodulatory glycoprotein of ∼14 kD purified from raw garlic was found to augment a delayed-type hypersensitivity response [11] and NK-cell activity in BALB/c mice when administered intraperitoneally [12]; further, the protein fraction was found to augment parasite engulfment and destruction of intracellular parasites by macrophages in vivo [13]. In another study, a 10-14 kD protein fraction was identified as responsible for induction of nitric oxide production, thus promoting the activation of reduced macrophage activity [14]. In all the aforementioned studies, the active components of the protein fraction of garlic possessing an immunomodulatory property have not been clearly defined or characterized.…”
Section: Introductionmentioning
confidence: 96%
“…An immunomodulatory glycoprotein of ∼14 kD purified from raw garlic was found to augment a delayed-type hypersensitivity response [11] and NK-cell activity in BALB/c mice when administered intraperitoneally [12]; further, the protein fraction was found to augment parasite engulfment and destruction of intracellular parasites by macrophages in vivo [13]. In another study, a 10-14 kD protein fraction was identified as responsible for induction of nitric oxide production, thus promoting the activation of reduced macrophage activity [14]. In all the aforementioned studies, the active components of the protein fraction of garlic possessing an immunomodulatory property have not been clearly defined or characterized.…”
Section: Introductionmentioning
confidence: 96%
“…Garlic possesses evident pharmacological properties, such as antimicrobial [16,17], antioxidant [18,19], and anticancer activities [20,21]. Garlic and its components have potent antiparasitic activities against many human and animal parasites [22], such as Leishmania [23,24], Schistosoma [25,26], Trypanosoma , Giardia , Entamoeba [27,28], and Plasmodium [29,30]. Allicin (diallyl thiosulfinate), rapidly converted from allin by allinase in crushed fresh garlic cloves, is a major component and thiosulphinate compound responsible for the biological activity of garlic [31].…”
Section: Introductionmentioning
confidence: 99%
“…23 Garlic is one of the most ancient vegetables and its medicinal used are dated back more 5,000 years. 24 In Greek, garlic has been used traditionally as pain relief. 14 It also has been used to treat toothache and struma.…”
Section: Discussionmentioning
confidence: 99%